2015
DOI: 10.1111/plb.12420
|View full text |Cite
|
Sign up to set email alerts
|

Biogeographic patterns of nutrient resorption from Quercus variabilis Blume leaves across China

Abstract: The variation in nutrient resorption has been studied at different taxonomic levels and geographic ranges. However, the variable traits of nutrient resorption at the individual species level across its distribution are poorly understood. We examined the variability and environmental controls of leaf nutrient resorption of Quercus variabilis, a widely distributed species of important ecological and economic value in China. The mean resorption efficiency was highest for phosphorus (P), followed by potassium (K),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 47 publications
(138 reference statements)
2
24
1
Order By: Relevance
“…The positive relationships between resorption (both in N and P) and absolute latitude for ECM trees were probably due to the relatively high resorption and the predominance of ECM trees in cold and high‐latitude areas. Previous studies also showed that ECM trees, such as Betula pubescens at four different sites in Sweden (Nordell & Karlsson, ) and Quercus variabilis in 16 provinces in China (Sun et al, ), had higher nutrient resorption at higher latitudes. Moreover, Oleksyn, Reich, Zytkowiak, Karolewski, and Tjoelker () found that even at the same site, ECM trees ( Pinus sylvestris ) from high latitudes still had higher nutrient resorption (both in N and P) than genotypes from low latitudes, suggesting that a more conservative nutrient use strategy for ECM trees may be a well‐conserved adaptation to relatively harsh (i.e., cold and wet) climates.…”
Section: Discussionmentioning
confidence: 77%
“…The positive relationships between resorption (both in N and P) and absolute latitude for ECM trees were probably due to the relatively high resorption and the predominance of ECM trees in cold and high‐latitude areas. Previous studies also showed that ECM trees, such as Betula pubescens at four different sites in Sweden (Nordell & Karlsson, ) and Quercus variabilis in 16 provinces in China (Sun et al, ), had higher nutrient resorption at higher latitudes. Moreover, Oleksyn, Reich, Zytkowiak, Karolewski, and Tjoelker () found that even at the same site, ECM trees ( Pinus sylvestris ) from high latitudes still had higher nutrient resorption (both in N and P) than genotypes from low latitudes, suggesting that a more conservative nutrient use strategy for ECM trees may be a well‐conserved adaptation to relatively harsh (i.e., cold and wet) climates.…”
Section: Discussionmentioning
confidence: 77%
“…Much research has been devoted to understand the nutritional control of nutrient resorption and several studies point to climatic effects on nutrient resorption (Oleksyn, Reich, Zytkowiak, Karolewski, & Tjoelker, 2003;Reich & Oleksyn, 2004;Sun et al, 2016;Yuan & Chen, 2009). However, little is known about the effects of ongoing climate change on this process (Brant & Chen, 2015, but see Aerts, Cornelissen, Van Logtestijn, & Callaghan, 2007;Norby, Long, Hartz-Rubin, & O'eill, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…However, little is known about the effects of ongoing climate change on this process (Brant & Chen, 2015, but see Aerts, Cornelissen, Van Logtestijn, & Callaghan, 2007;Norby, Long, Hartz-Rubin, & O'eill, 2000). Variation in N and P resorption along large environmental gradients has been attributed to changes in mean annual temperature and mean annual precipitation (Brant & Chen, 2015;Du et al, 2017;Sun et al, 2016;Yuan & Chen, 2009). At large spatial scales, plant nutrient concentrations (N, P, K) generally decrease with increasing mean annual temperature and decreasing mean annual rainfall (Reich & Oleksyn, 2004;Sardans et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Increasing demands for timber products have promoted more research on plantations, which require more nutrients for their rapid growth [15,16]. Nutrient resorption in planted forests is less studied, since many synthesis studies excluded data of nutrient resorption from plantations [5,7,17]. Additionally, few nutrient-resorption studies have separated planted forests from other forest types [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%